Lemon Balm and Corn Silk Mixture Alleviates Metabolic Disorders Caused by a High-Fat Diet - Il-Je Cho; Joung-Hoon Shin; Beom-Rak Choi; Hye-Rim Park; Jeong-Eun Park; Seong-Hwa Hong; Young-Sam Kwon; Won-Seok Oh; Sae-Kwang Ku (MDPI AG, 2022)
We recently reported that varying combination ratios of lemon balm (Mellissa officinalis L.) and corn silk extracts (Stigma of Zea mays L. fruit) could reduce the obesity caused by a high-fat diet (HFD). The present study investigated the dose-dependent effect of a 1:1 (w:w) mixture of lemon balm and corn silk extracts (M-LB/CS) on HFD-mediated metabolic disorders and compared the effect with metformin. Oral administration of 50-200 mg/kg of M-LB/CS for 84 days significantly inhibited HFD-induced body weight gain, adipocyte hypertrophy, and lipogenic gene induction without affecting food consumption in mice. Biochemical analyses showed that M-LB/CS blocked abnormal lipid accumulation in the blood by escalating fecal lipid excretion. In addition, M-LB/CS prevented HFD-mediated pancreatic atrophy, decreased the number of insulin- and glucagon-immunoreactive cells, and inhibited increases in glycated hemoglobin, glucose, and insulin. Moreover, M-LB/CS also reduced hepatic injury, lipid accumulation, gluconeogenesis, and lipid peroxidation in parallel with the induction of AMP-activated protein kinase and antioxidant enzymes. Furthermore, M-LB/CS protected the kidney by inhibiting tubular vacuolation and reducing serum creatinine and blood urea nitrogen levels. The prophylactic effect of 100 mg/kg M-LB/CS-administration was comparable to that of metformin. Therefore, M-LB/CS may be an alternative option for managing obesity and its related metabolic disorders.